Teacher’s Talk and Students’ Motivation in an English Classroom: Insights from a Case Study - Zahratun Nufus; Nur Ifadloh; Alaa Hussein Jafar Al-Anbari; Sanjay Kumar Jha; Sayyidah Shalehah (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
The context of English as a Foreign Language (EFL) learning, teacher’s talk is crucial to control classroom interactions and enhance language learning. This qualitative case study investigated how seventh-grade female students were motivated to learn English as a result of their teacher’s talk. The study used the Flanders Interaction Analysis Category System (FIACS) to classify teacher’s talk through classroom observations and interviews. The results revealed that giving instructions, asking questions, and expressing encouragement or praise were the most common ways teachers communicated. Students’ motivation and engagement were greatly enhanced by these verbal techniques. On the other hand, engagement was often hampered by the lack of student-centered discourse, such as accepting students’ opinions or using harsh criticism. A key novelty of this study is the exploration of gender dynamics, specifically how a male teacher communicates with an all-female class in an Islamic educational setting, a context rarely examined in prior research. The study highlights the importance of teacher communication strategies in fostering a supportive and motivating EFL classroom environment.